Endoscopic Sponge Vacuum Therapy for Large Infected Esophagus Pleural Fistula - Bhaware, Bhushan; Mukewar, Shrikant; Daswani, Ravi; Gawande, Atul; Mukewar, Saurabh (Journal of Digestive Endoscopy, 2022)
A 50-year-old man with hypothyroidism was diagnosed with severe pneumonia secondary to the SARS-CoV-2 virus with an HRCT CORAD score of 18/25 in September 2020. From the records, the patient appeared to have developed spontaneous esophageal perforation. In view of his poor general condition, he was treated with endoscopic sponge vacuum therapy (EVT). EVT is a novel approach for treatment for a closed cavity. Also, very few studies exist in the literature in regard to this procedure.
Keywords: endoscopic vacuum therapy; esophageal pleural fistula; endoscopic sponge; Boerhaave's syndrome